Case theory in Kurdish and Arabic A comparative study (Raparin Journal of Humanities (RJH), 2023)
This research has been written under the title: The Grammatical Case in Kurdish and Arabic Languages: A Comparative Study. The research aims to identify points of similarities and differences between the grammatical case in Standard Arabic and Kurdish language (Sorani dialect/Sulaymaniyah subdialect).The importance of the research lies in its usage - for the first time – of the modern transformational generative theory to compare Kurdish and Arabic languages. The research – with excluding the summary and introduction - consists of two axes:  The first axis talks about the principles of the grammatical case model. As for the second axis deals with grammatical case patterns and their application in the two mentioned languages.The search ends with displaying the results and a list of sources and references.